1997
DOI: 10.1002/maco.19970480105
|View full text |Cite
|
Sign up to set email alerts
|

Development and microstructure of the Al‐depleted layer of oxidized TiAl

Abstract: The microstructure and development of the scale of oxidized y-TiAl were studicd in cross section by electron microscopy and metallographic techniques. Ti-SO(at.%)Al samples wcre oxidized at 900°C in air for various times and especially the evolution of the scale/metal interface was investigated. The formation of the aluminium depleted subsurface layer could be observed after 1 h and develops from a single phase to a two phase region with longer exposure times. The single phase region is visible up to I00 h and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The significant solubility and diffusivity of oxygen in the am-Al 0.44 Zr 0.56 alloy substrate relates to the intrinsically high solubility and diffusivity of oxygen in pure crystalline (a-)Zr, 2 which has an oxygen solubility of as high as 28.6 at.% in its pure form at 500°C. A similar high oxygen solubility ($7 at.% at 900°C [45]) was found in a 2 -Ti 3 Al, which relates to the high oxygen solubility in a-Ti (32 at.% O at 900°C) [28,46]. The large O solu- Table 1.…”
Section: Stage I: Amorphous Oxide-layer Growthmentioning
confidence: 79%
See 1 more Smart Citation
“…The significant solubility and diffusivity of oxygen in the am-Al 0.44 Zr 0.56 alloy substrate relates to the intrinsically high solubility and diffusivity of oxygen in pure crystalline (a-)Zr, 2 which has an oxygen solubility of as high as 28.6 at.% in its pure form at 500°C. A similar high oxygen solubility ($7 at.% at 900°C [45]) was found in a 2 -Ti 3 Al, which relates to the high oxygen solubility in a-Ti (32 at.% O at 900°C) [28,46]. The large O solu- Table 1.…”
Section: Stage I: Amorphous Oxide-layer Growthmentioning
confidence: 79%
“…The measured AES sputter-depth profiles after thermal oxidation of the am-Al 0.44 Zr 0.56 alloy for 15,30,45,180 and 240 min at 560°C are shown in Fig. 7a-f, respectively.…”
Section: Depth-resolved Chemical Constitutionmentioning
confidence: 99%
“…It should be noted that such extensive nitride formation and Al enrichment at the metal/scale interface does not appear to occur under shorter term, higher temperature exposure conditions. For example, Dettenwanger et al [14] report Al depletion and Z/X phase formation at the metal/scale interface for oxidation of Ti-50Al at 900°C in air, which suggests a change in oxidation mechanism between 900°C and 700°C for binary γ-TiAl alloys. On the other hand, Magnan et al, on nitridation of TiAl at 1000ºC reported the formation of a surface nitride scale and an Al-enriched subscale [21].…”
Section: Oxidation At 704°c -7000 H -In Airmentioning
confidence: 99%
“…This intermixed region is followed by a bright Al-depleted (Ti-rich)/O-rich layer right at the metal/scale interface; its average microprobe chemistry is 58 Ti, 28 Al, 10.8 O and 2.3 Cr. This layer is speculated to be the Z/X phase described in [12][13][14]. No N-enrichment was detected at the subscale, although Haanappel et al [8,22] reported the presence of Ti-nitrides after 150h at 700°C in Ti48Al-2Cr.…”
Section: Oxidation At 704°c -7000 H -In Airmentioning
confidence: 99%
See 1 more Smart Citation